(untitled) (Faridpur Medical College Journal, 2011)
Diabetes Mellitus (DM) is a public health challenge all over the world. Recent evidence suggests that there is a positive association between smoking and the risk of diabetes. This descriptive cross-sectional study was conducted from March to June 2008 at BIRDEM Hospital, Shahbagh, Dhaka to find out pattern of tobacco consumption among diabetic patients. Age of the respondents was >15 years. With purposive sampling total 255 respondents were selected. Data was collected through face-to-face interview with structured questionnaire. Out of 255 respondents, 51.4% consumed deferent type of tobacco. Smoker was 63.36% and smokeless tobacco user was 52.67%. The highest (45.80%) had habit of smoking, 36.64% had habit of smokeless tobacco and 17.56% had habit both types of tobacco consumption. The highest smoking and smokeless tobacco consumption found within 50-60 years age group. Total 60.80% male had smoking habit and 32.82% female were smokeless tobacco consumer but no female was smoker. Twenty nine percent tobacco consumers were primarily educated, 16.08% service holders were tobacco consumer and 13.75% service holders were smoker. Among respondents lung diseases and heart diseases were common (78.54.0% and 49.36%). Respondents who consumed tobacco were suffered (74.36%) more complication than non-tobacco consumer (25.64%). So an effective awareness program is required to discourage the consumption of tobacco to protect diabetic patients. Key words: Diabetes mellitus; Smoking; Tobacco DOI: http://dx.doi.org/10.3329/fmcj.v6i2.9210 FMCJ 2011; 6(2): 95-99